Intracluster stereochemistry in van der Waals complexes: steric effects in ultraviolet photodissociation of state-selected Ar-HOD/H2O. - Votava, O; Mackenzie, S; Nesbitt, D (2004)
High-resolution IR-UV multiple resonance methods are employed to elucidate the photodissociation dynamics of quantum state-selected Ar-HOD and Ar-H(2)O van der Waals clusters. A single mode pulsed OPO operating in the region of the OH second overtone is used to prepare individual rovibrational states that are selectively photodissociated at specific excimer wavelengths. Subsequent fluorescence excitation of the resulting OH (OD) fragments yields dynamical information on the photofragmentation event and any resulting intracluster collisions. This technique is used to characterize spectroscopically the Pi(1(01)), nu(OH)=3<--Sigma(0(00)), v(OH)=0 overtone band of the Ar-HOD complex with an origin at 10648.27 cm(-1). The effects of Ar complexation on the dissociation dynamics are inferred by comparison of the OD photofragment quantum state distributions resulting from dissociation of single rovibrational states of the complex with those from isolated HOD photodissociation. The important role played by the initial internal state of the complex is demonstrated by comparison of the current Ar-HOD data with previously published results for the Ar-H(2)O Sigma(0(00))[03(-)> state. We interpret the dramatic differences in the dynamics of the two systems as manifestations of the nodal structure of the vibrational state in the parent complex and the way in which it governs the collision probability between the Ar atom and the escaping photofragments.